Analisis Numerik Propagasi Soliton Dalam Serat Optik - Freddy P. Zen; Wahyu Hidayat; Ridwan Shiddiq (Institut Teknologi Bandung, 2002)
Soliton propagation and some related parameters are considered by using Nonlinear Schroedinger Equation (NLS) with fiber loss and higher order dispersion term as dynamical representation in optical fibers. By using the Split-Step Fourier Method we showed that nonlinear parameter, fiber loss, higher order dispersion term influence the soliton propagation behavior in optical fibers. From simulation result yields that dispersion effect and nonlinearity compensate each other if dispersion and nonlinear length scales nearly equal. Whereas fiber loss reduced intensity and higher order dispersion term influence symmetry profile of the pulses as long as propagation.